Spinning up ServiceNow: IT Service Managers' Guide to Successful User Adoption - Kahlout, Gabriele (SpringerLink, 2017)
Learn how to onboard ServiceNow ITSM tools by evangelizing, educating, and coordinating your organization's service desk, developers, and stakeholders. Drawing on his own story of lessons learned in spinning up the adoption of ServiceNow throughout the Al Jazeera Media Network, application architect Gabriele Kahlout shows IT service managers how to launch automated ServiceNow ticketing tools in seamless integration with their organization's existing email and Active Directory.Spinning Up ServiceNow: IT Service Managers' Guide to Successful User Adoption shows you how to orchestrate your IT service desks and developers to facilitate the adoption and consumption of IT services by all users, supporting their various business needs while optimizing human-computer interaction and minimizing stress and productivity loss arising from poor human-system design.What You'll LearnQuick-start ServiceNow in a matter of days with the minimum configuration required to start processing tickets via emailAvoid the teething problems that can spoil your users’ onboarding experience with ServiceNowAutomate the process of scaling up new teams into ServiceNowShape your users' experiences so that they retain their familiar bearings in email and Active Directory while welcoming the power of ServiceNow enhancementsCreate a strategy to avoid common pitfalls that sabotage ITSM programsWho This Book Is For IT managers charged with implementing ServiceNow ITSM suites in their organizations and business analysts determining the requirements for such implementation. The secondary readership is system administrators and developers involved in ITSM.